How Community and Peer Perceptions Promote College Students’ Pro-Social Bystander Actions to Prevent Sexual Violence - Banyard, Victoria L. (Journal of interpersonal violence, 2021)
The prevalence of sexual violence crimes on U.S. college campuses is prompting institutions of higher education to increasingly invest in centers to support survivors and programs to prevent the violence before it happens. Understanding bystanders to sexual violence and what may motivate them to step in and help is a promising prevention strategy. The purpose of this study was to understand how potential active bystanders’ (first-year college students) perceptions of community (including a sense of one’s influence in the community and positive peer norms for helping) and individual beliefs about self (including sense of responsibility and self-efficacy) affect their self-reports of performing bystander behavior to address sexual violence risks. Participants were 948 students at two different universities (one a rural, primarily residential campus and the other an urban, mostly commuter campus) in the northeastern United States. Regression and path analysis quantitative results suggest that individual-level characteristics may mediate some of the impact that community-level norms and perceptions have on bystander outcomes, explaining some of the mixed findings in previous research. Prevention strategies should work to change community norms and perceptions of mattering and perceptions of community influence in addition to the more traditional focus on individual-level violence specific attitudes.